0648 Shift Work Sleep Disorder And Associated Psychosocial Factors Among Chinese Practice Nurses: A Prospective Study. (27th April 2018) - Shi, X; Fan, F
Abstract: Introduction: Shift work is associated with sleep problems and impaired health. The aim of the present study was to investigate the prevalence of shift work sleep disorder (SWSD) and predictors of developing SWSD in a sample of Chinese practice nurses. Methods: This is a longitudinal study with two waves of data collection. The subjects were 664 practice nurses who had never worked on a shift before, with a mean age of 17.83 years (SD=1.56) from a secondary health school of Guangdong Province, China. Participants completed an extensive battery of scales concerning work, health and individual differences through online methods two weeks before the shift (baseline) and three months after the shift (T3mon ). SWSD was determined based on signiﬁcant sleep disturbance and/or excessive sleepiness in the context of working in a shift schedule. Multivariate logistic regression was used to examine predictors of developing SWSD. Results: The prevalence of SWSD was 35.8% among shift working nurses. Multivariate logistic regression analyses found significant associations between SWSD and flexibility (OR=0.93, 95%CI 0.88–0.98, languidity (OR=1.09, 95%CI 1.04–1.14), perceived stress (OR=1.08, 95%CI 1.03–1.14), backward rotating shift schedule (OR=1.63, 95%CI 1.10–2.43), a night-shift nap (OR=0.61, 95%CI 0.41–0.90), and difficulties in emotion regulation (OR=1.03, 95%CI 1.01–1.05) even after controlling insomnia at the baseline. Conclusion: The prevalence of SWSD was high in practice nurses. Based on the above mentioned results, hospital managers and psychologist need to provide appropriate and targeted mental health interventions in order to improve nurses' clinical performance and personal health status. Support (If Any): no.